2013
DOI: 10.4236/ojepi.2013.34028
|View full text |Cite
|
Sign up to set email alerts
|

The association between ADHD and eating disorders/pathology in adolescents: A systematic review

Abstract: Background: Attention-Deficit/Hyperactivity Disorder (ADHD), one of the most common neurodevelopmental conditions of childhood, is associated with high rates of mood and behavioral disorders. Preliminary evidence suggests that ADHD may also be associated with eating disorders (ED) or eating pathology (EP). This systematic review synthesizes the extant published literature on this association among youth ages 12 -21 years. Methods: Literature searches were performed using Medline, Ovid/Psych Info, Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Our findings are consistent with those of Graziano and colleagues (2013) who identified a longitudinal association between self-regulation difficulties early in life and the development of body image and eating concerns in preadolescent years. We speculate that behavioral dysregulation in particular may have strong associations with body image and other eating behaviors due to the breakdown of attentional and inhibitory processes previously associated with body dissatisfaction and eating behaviors (Curtin, Pagoto, & Mick, 2013; Gowey, Stromberg, Lim, & Janicke, 2015), such that body dissatisfaction may be developed or perpetuated as a result of difficulty inhibiting unpleasant repetitive thoughts about one’s body or perhaps biased attention to these unpleasant thoughts and feelings.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings are consistent with those of Graziano and colleagues (2013) who identified a longitudinal association between self-regulation difficulties early in life and the development of body image and eating concerns in preadolescent years. We speculate that behavioral dysregulation in particular may have strong associations with body image and other eating behaviors due to the breakdown of attentional and inhibitory processes previously associated with body dissatisfaction and eating behaviors (Curtin, Pagoto, & Mick, 2013; Gowey, Stromberg, Lim, & Janicke, 2015), such that body dissatisfaction may be developed or perpetuated as a result of difficulty inhibiting unpleasant repetitive thoughts about one’s body or perhaps biased attention to these unpleasant thoughts and feelings.…”
Section: Discussionmentioning
confidence: 95%
“…While some studies have found similar rates of psychiatric comorbidity in males and females [ 8 , 9 , 20 , 21 ], others found higher rates in males compared to females (e.g., [ 13 , 18 ]) and yet others found lower rates of comorbidity among males [ 2 , 23 ]. Looking specifically at attention deficit hyperactivity disorder (ADHD), a review article by Curtin, Pagoto and Mick [ 24 ] showed that five out of eight studies found an association between ADHD and ED or eating pathology in adolescents. Although ADHD has a male preponderance in the general population [ 25 ], half of the studies included in the review were based solely on female samples and one of the studies failing to find an association was based predominantly on males.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the prevalence of excess weight recorded by measuring BMI and perceived body image have clinical implications, including eating disorders. This aspect should be considered in efforts to advance guidance to adolescents and their families [21].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to prevent childhood and adolescent obesity should tackle specific determinants, within the set of personal, behavioural and socio-environmental factors, such as promotion of a positive image of the body, and reduction of unhealthy weight controlling behaviours [22].…”
Section: Discussionmentioning
confidence: 99%